Analisis Sistem Antrian pada Proses Pelayanan Konsumen di Warung Ayam Geprek Najwa Menggunakan E-WOM - Soniya, Yeni; Pratiwi, Ratna; Ramadhani, Almy; Mth, Sri Rezky Aprilawati Br. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to determine the effect of e-Wom, food quality and service quality on Purchase Satisfaction at Najwa geprek chicken stall. This research method was quantitative through an online questionnaire with a total of 145 respondents. The data used for the analysis of this queuing system is primary data, which is in the form of customer arrival time data and service time data (server), for time measurement carried out using the help of a stopwatch. The results of data analysis showed that the enthusiasm of Rantauprapat residents towards Najwa geprek chicken stall was very high, this made Najwa geprek chicken stall does not empty of visitors, resulting in queues